Impacto de la aplicación del código orgánico de la producción comercio e inversiones en empresas alimenticias, de la ciudad de Latacunga, provincia de Cotopaxi del periodo 2011 al 2012 - Alarcón Argudo, Paola Katherine (2015)
In this paper a quantitative and qualitative study of the impact of the implementation of the Organic Code of Production, Trade and Investment in food businesses in the city of Latacunga and what were the benefits or tax incentives to which they agreed is performed.